The Correlation Between Grammar Ability and Students Speaking Skill at 10th Grade Studetns of MAN Lima Puluh Kota - Umami, Khairat; Kardena, Absharini; Safitri, Loli; Amiza, Elsi (Pusdikra-Publishing.com, 2024)
The background of this research was because of several problems that students had that related to grammar and speaking, the problem was students' average in speaking was good while students' average in grammar was low, and some students had difficulty in choosing correct vocabulary in exercise, and the dominance of students with good speaking and poor grammar based on teacher scores. As a result, the researcher wanted to find out the correlation between grammar ability and students' speaking skill at 10th grade students of MAN Lima Puluh Kota. The design of this research was correlational research, with the population of this research was all of the 10th grade students of MAN Lima Puluh Kota in academic year 2022/2023, which consist of 4 classes, with 75 students and using total sampling as the sample because of the population are less than 100 students. The instrument of this research was grammar test and speaking test. The grammar test was multiple choice with consist 25 number and speaking test was students divided into several groups and make a short dialog then perform it. This research was carried out in October 2023. To find out that grammar ability and students speaking skill corralate or not, and the researcher used Pearson Correlation. The result of this research by using Pearson Coefficient between the variables was 0,566 which indicated a bit low correlation, the correlation direction was positive and the correlation magnitude between the variables was a bit low correlation, because there some students had a score in speaking was higher than grammar score.